A 10-year review of pediatric uveitis at a Hispanic-dominated tertiary pediatric ophthalmic clinic - Dajee KP (Dove Medical Press, 2016)
Kruti P Dajee,1,2 Jennifer Landau Rossen,1 Monica L Bratton,1,2 Jess T Whitson,1 Yu-Guang He1,2 1Department of Ophthalmology, UT Southwestern Medical Center, 2Department of Ophthalmology, Children’s Medical Center of Dallas, Dallas, TX, USA Purpose: The aim of this study was to evaluate the characteristics and outcomes of pediatric uveitis cases at a large tertiary referral center in Dallas, TX, USA.Materials and methods: The authors performed a retrospective chart review between 2001 and 2011 to identify children with uveitis.Results: A total of 46 children (68 eyes) with uveitis were identified. Sixty-seven percent were Hispanic, and the mean age was 9.2 years. The majority of cases were idiopathic (74%). Anterior uveitis accounted for 42% of cases followed by intermediate uveitis/pars planitis (33%), posterior uveitis/retinitis (7%), and panuveitis (20%). Most patients were treated with corticosteroids (98% topical), 52% with systemic immunosuppression therapy, and 30% with surgery. Complications occurred in 74% of patients, with the most common complication being cataract development (26%), followed by posterior synechiae (24%). Twenty-four percent of patients had recurrences. Hispanic patients had worse visual acuities at presentation (P-value =0.073) and follow-up (P-value =0.057), compared to non-Hispanic patients.Conclusion: Pediatric uveitis cases seen in a large center in Dallas were largely idiopathic, had commonly developed complications, and were associated with worse visual outcomes in Hispanic patients. Keywords: pediatric ophthalmology, uveitis, outcomes, Dallas, Hispanic